Innovative Molecular Design for a Volume Oriented Component Diagnostic: Modified Magnetic Nanoparticles on High Performance Yarns for Smart Textiles1. Issue 10 (18th September 2014) - Bartusch, Matthias; Hetti, Mimi; Pospiech, Doris; Riedel, Maria; Meyer, Joerg; Toher, Cormac; Neu, Volker; Gazuz, Igor; Shagolsem, Lenin S.; Sommer, Jens‐Uwe; Hund, Rolf‐Dieter; Cherif, Chokri; et al.
<x xml:space="preserve">Abstract</x> A novel way for destruction‐free, volume‐oriented component diagnostics is reported. Surface‐modified magnetic nanoparticles are applied for impregnation of plasma‐activated UHMW PE textiles, which are embedded into an epoxy matrix. Supported by simulations, this comprehensive study from single molecules to composites extends the knowledge of molecular interactions at polymer interfaces and broadens the application of non‐destructive methods. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>